Chemoselective Carbenoid Reactions of Furan/Thiophene/Pyrrole Ring Containing Carbonyl and Conjugated Carbonyl at Their 2‐Positions - Seyma Gungor, Fusun; Merey, Gokce; Anac, Olcay (Wiley, 2020)
Abstract Several furyl/thiophenyl/ N ‐methylpyrrolyl cores having aldehyde/ketone/ene‐biscarbonyl/diene‐biscarbonyl functions at their 2‐positions were reacted with diazocarbonyl compounds in the presence of metal catalysts. Between the two possible reaction pathways which may take place either on the 2‐substituent of hetaryl or on the core structure, only one of them was dominant for each reaction depending on substituents. Accordingly, in the reaction of thiophene‐2‐carbaldehyde with diazo compounds we obtained epoxy derivatives. On the other hand, dimethyl diazomalonate and furyl‐ene‐diketo/ N ‐methylpyrrolyl‐ene‐diester yielded only novel dihydrofuran derivatives via [1,5]‐electrocyclic ring closure. However, the reactions of 2‐ene/diene‐diester functionalized furans with dimethyl diazomalonate resulted polymethoxycarboxylate‐substituted oxo‐polyenes chemo‐specifically in good yields.
Keywords: carbenes; diazo compounds; hetaryl; oxo-polyene; carbenoids